Gender Differences in Education, Career Choices and Labor Market Outcomes on A Sample of OECD Countries - Flabbi, Luca (World Bank, 2012)
In most OECD countries gender differentials in the labor market have experienced a steady reduction in the 1970s and 1980s. Starting with the 1990s, however, the convergence between the labor market performance of men and women has essentially stopped. As a result, gender differentials in the labor market are still significant and persistent. At the same time, differences in pre-labor market characteristics, in particular education, have decreased and in most OECD countries women now acquire more education than men. However, if the differences in the amount of education acquired by men and women are small, the differences in the type of education (such as the field of study, major or other characteristics of the study programme) are still large.